Simultaneous spontaneous bilateral quadriceps tendon rupture with secondary hyperparathyroidism in a patient receiving hemodialysis: A case report. Issue 10 (March 2019) - Wu, Weiqian; Wang, Chongyang; Ruan, Jianwei; Wang, Haibao; Huang, Yang; Zheng, Wenbiao; Chen, Fanghu
Abstract: Rationale: Simultaneous spontaneous bilateral quadriceps tendon rupture is a rare orthopedic injury; its initial diagnosis is misdiagnosed in up to 50% of patients with secondary hyperparathyroidism. Early diagnosis and surgical repair are important to achieve an excellent functional outcome. Patient concerns: We report a case of simultaneous spontaneous bilateral quadriceps tendon rupture associated with secondary hyperparathyroidism. Diagnosis: Magnetic resonance imaging showed that the quadriceps tendon was completely ruptured at the osteotendinous junction. We then found bilateral quadriceps tendon rupture during the operation. Interventions: The patient underwent successful tendon repair surgery. Outcomes: The 31-year-old female patient regained full active movement of both knee joints and was able to participate in her activities of daily living. Lessons: Simultaneous spontaneous bilateral quadriceps tendon rupture in a patient with secondary hyperparathyroidism (undergoing hemodialysis) is a rare orthopedic injury that can be easily overlooked at the initial presentation. Early diagnosis and surgical repair is important to achieve an excellent functional outcome. For patients with secondary hyperparathyroidism receiving hemodialysis, strict systematic treatment of hyperparathyroidism is needed to prevent rupture or re-rupture of the quadriceps tendon.